The effects of Phyllostachys edulis root systems on soil: insights from mechanical and hydrological testing - Yunzhao Lin; Zuteng Zhu; Wenbin Jian; Yilong Wu; Haolong Kang; Xiufeng Fan; Xin Zhong (Geomatics, Natural Hazards & Risk, 2025)
To investigate the effects of Phyllostachys edulis on shallow landslide, a series of experiments were conducted at P. edulis forest landslide sites. These experiments included root tensile tests and chemical composition analysis, in situ direct shear tests of root-soil composites under varying moisture conditions, in situ double-ring infiltration tests, and root profile survey. The tensile strength of P. edulis roots ranged from 11.6 to 34.10 MPa, showing a negative power-law correlation with increasing root diameter. Root diameter exhibited a significant positive power-law correlation with cellulose and hemi-cellulose content and a significant negative power-law correlation with lignin content; As volumetric moisture content increased from 20 to 45%, the shear strength of the root-soil composite initially rose and then declined, peaking at ∼25% moisture content. Beyond this threshold, shear strength decreased significantly as moisture content rise; P. edulis roots significantly enhanced soil infiltration performance. The infiltration rate of rooted soil at 0 m was the highest across all infiltration stages, with its saturated hydraulic conductivity being 3.1 times greater than that of soil without roots; Rainfall-induced water infiltration reduced the shear strength of the root-soil composite. Additionally, the infiltration-enhancing effect of roots made the interface between root-containing and root-free soil more susceptible to becoming a slip surface.